2022
DOI: 10.18235/0004042
|View full text |Cite
|
Sign up to set email alerts
|

Closing Gender Gaps in the Southern Cone: An Untapped Potential for Growth

Abstract: In this volume, we study gender gaps in the Southern Cone countries which include Argentina, Brazil, Chile, Paraguay, and Uruguay. We assess the importance of gender inequalities and present evidence on their economic consequences, their drivers, and the policy tools that can contribute to mitigating them. Gender gaps in access to public services, human capital accumulation, and the labor market limit overall productivity and economic growth, and policies that mitigate these inequalities have the potential to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…The literature has left evidence of this behaviour in women micro-entrepreneurs, considering as a relevant factor the lack of education, access to resources and time available for their responsibilities at home (Sendra-Pons et al, 2021). Specifically, women triple the hours per week on domestic activities compared to men and are under-represented in formal employment (Inter-American Development Bank, 2022). In this research, we want to evaluate the gender difference in micro-enterprises, especially in those businesses in which the lack of resources (human and financial) leads their owners to improvise and be creative using public spaces where they offer their products and services (Mart ınez and Young, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature has left evidence of this behaviour in women micro-entrepreneurs, considering as a relevant factor the lack of education, access to resources and time available for their responsibilities at home (Sendra-Pons et al, 2021). Specifically, women triple the hours per week on domestic activities compared to men and are under-represented in formal employment (Inter-American Development Bank, 2022). In this research, we want to evaluate the gender difference in micro-enterprises, especially in those businesses in which the lack of resources (human and financial) leads their owners to improvise and be creative using public spaces where they offer their products and services (Mart ınez and Young, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on informality in Latin America are very scarce, which makes this research relevant even more in times of COVID-19, when the gender gap has widened, with married women with children being the ones who have achieved greater prominence in the informal business sector (Inter-American Development Bank, 2022). Taking into account the indicator of discrimination against women in social institutions (Social Institutions and Gender Index -SIGI), it is found that in 2019 Colombia was the Latin American country with the lowest rate of discrimination, registered at 15%, followed by Brazil (21.2%) and Bolivia (21.4%); while the countries with the highest rate of discrimination against women were Mexico (29%), Paraguay (32.8%) and Chile (36.1%) (Organization for Economic Cooperation and Development [OECD], 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La participación de las mujeres en el mercado laboral se ha incrementado en las últimas décadas, y con ello su visibilidad como protagonistas importantes de la economía. Sin embargo, aún existen desafíos y brechas a los que se enfrentan cuando allí compiten (Frisancho y Queijo, 2022). Por otro lado, la evidencia muestra que la crisis generada por el COVID 19 y sus efectos en el mercado laboral afectaron en mayor proporción a las mujeres en América Latina y el Caribe, profundizando aún más las brechas y revirtiendo los avances antes logrados (Bustelo, Suaya y Vezza, 2021).…”
Section: Introductionunclassified
“…En los últimos años, América Latina y el Caribe (ALC) han experimentado cambios significativos en los roles tradicionalmente asignados a hombres y mujeres. Se ha observado un aumento en la representación política de las mujeres, así como un incremento en sus niveles de educación y participación en el mercado laboral (Frisancho y Queijo, 2022). A pesar de estos avances, persisten desafíos en lo que respecta a la inclusión laboral de las mujeres y sus oportunidades de desarrollo profesional 1 .…”
Section: Introductionunclassified